Cytogenetic study of the redtail bagrid (Hemibagrus wyckioides) using conventional staining and NOR-banding techniques - Getlekha, Nuntaporn; Sribenja, Kamika (Food Agricultural Sciences and Technology, 2026)
A karyotype and standard idiogram analysis of the redtail bagrid (Hemibagrus wyckioides) from the Mae Klong River Basin, Kanchanaburi province, was conducted using samples from seven males and eight females. Chromosomes were directly extracted from kidney tissue and stained with Giemsa stain and NOR-banding. The results showed that the redtail bagrid had 58 diploid chromosomes (2n) and 102 fundamental chromosomes (NF). The karyotype included 6 large metacentric, 8 large submetacentric, 6 large acrocentric, 16 medium metacentric, 4 medium submetacentric, 4 medium acrocentric, 8 medium telocentric, and 6 small telocentric chromosomes, respectively. No chromosomal differences were observed between the sexes. NOR staining identified one pair of NOR loci located at the telomeric region of the short arm of a metacentric chromosome. This study is the first cellular genetic analysis of the redtail bagrid and provides valuable data for the taxonomic classification of bagrid catfish. Additionally, the findings can serve as a foundation for the conservation of catfish genetic resources and future studies on chromosomal evolution. The karyotype formula of H. wyckioides is 2n (58) = Lm6+Lsm8+La6+Mm16+Msm4+Ma4+Mt8+St6